Georgia : Technical Assistance Report-Residential Property Price Indices Mission. (IMF Staff Country Reports; Country Report, 2020)
This Technical Assistance (TA) report on Georgia is on Residential Property Price Indices (RPPI) Mission. The contents of this report constitute technical advice provided by the IMF staff to the authorities of Georgia in response to their request for TA. The Second Phase of the G-20 Data Gaps Initiative and guidance on Financial Soundness Indicators identify RPPI as a critical ingredient of financial stability policy analysis and macroprudential measures. National Statistics Office of Georgia (Geostat) is aiming at compiling a quarterly RPPI covering new flats and new detached houses for the capital city, Tbilisi. The mission implemented successfully the programs developed in R based on the IMF's draft for the RPPI Practical Compilation Guide with the available data. The mission provided some guidance on the use of scanner data (SD) on the consumer price index (CPI) compilation. As per request of the Geostat Director, the mission also addressed the use of SD. The introduction of SD should be made on a stepwise approach to avoid huge impacts on the CPI and to make it more manageable, reliable, and safe.